2020
DOI: 10.1002/adma.202001238
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Opportunities and Challenges for Nanocellulose Spinning

Abstract: In comparison to natural fibers, such as silk-, cotton-, or wool-fibers, man-made fibers refer to fibers fabricated from either synthetic or natural polymers. Man-made fibers from synthetic polymers (the largest volume of man-made fibers) are mainly produced from fossil-based resources, such as oil or gas. Examples of commonly used polymers are polyamides, polyesters, polyethylene, or polyurethanes. As a result of a century of developments within the area of polymer science and processing, it is currently poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 110 publications
1
48
0
Order By: Relevance
“…An example, where flow-focusing with a detached core is achievable is the hydrodynamic focusing and spinning of filaments from nanocellulose. 31,[37][38][39] As an example, by applying the double flow-focusing technique, Mittal et al 37 demonstrated how the first focusing with the buffer caused an alignment of cellulose nanofibers (CNFs), and a second focusing with a gelation agent could make the CNFs aggregate in an aligned state. Drying this gel thread resulted in filaments exceeding mechanical properties of any known natural material.…”
Section: Introductionmentioning
confidence: 99%
“…An example, where flow-focusing with a detached core is achievable is the hydrodynamic focusing and spinning of filaments from nanocellulose. 31,[37][38][39] As an example, by applying the double flow-focusing technique, Mittal et al 37 demonstrated how the first focusing with the buffer caused an alignment of cellulose nanofibers (CNFs), and a second focusing with a gelation agent could make the CNFs aggregate in an aligned state. Drying this gel thread resulted in filaments exceeding mechanical properties of any known natural material.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, cellulose nanofibrils (CNFs) are gaining more attention as a substitute for glass or carbon fibers due to their particular mechanical properties in combination with sustainable resources and biodegradability. [8] In detail, nanocellulose extracted from wood was shown to be a good reinforcing agent in polymer nanocomposites, while retaining flexibility, lightweight, and mechanical stiffness. [9,10] Chemical functionalization of nanocellulose can be used to further tailor barrier performance of films which might be of crucial benefit for considering nanocellulose as a template for organic electronics.…”
Section: Introductionmentioning
confidence: 99%
“…2D films in photonic applications 16 . The main advantage of CNFs, are their inherent ability to form volume-spanning networks at very low concentrations [17][18][19][20][21][22] , making them highly desirable as building blocks in membranes, barriers, aerogels, foams 1,2,4 , 3D-printed materials 23 and also for making filaments that can be used for reinforcing new biobased composites and high-performance textiles 22,[24][25][26][27][28][29][30][31][32] The properties of materials produced from the bottom-up reassembly of CNCs and CNFs are highly dependent on their spatial and orientation distributions within the material, which in turn are set by the processing conditions 14,29 . A common route for controlling the nanostructure of the final product includes hydrodynamic alignment with subsequent assembly (transition from dispersion to gel, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A common route for controlling the nanostructure of the final product includes hydrodynamic alignment with subsequent assembly (transition from dispersion to gel, i.e. gelation) by neutralizing the electrostatic repulsion between nanoparticles through the addition of salts or acids 25,28,29 . It has been found during spinning filaments from CNFs, that a system, which is aligned through a pure extensional flow with no shear, is highly desirable to obtain optimal mechanical properties 28,29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation